2003
DOI: 10.1300/j031v15n02_02
|View full text |Cite
|
Sign up to set email alerts
|

Demography of Indian Aging, 2001-2051

Abstract: India is the second largest country in the world, with 72 million elderly persons above 60 years of age as of 2001, compared to China's 127 million. One of the objectives of this paper is to assess the emerging scenario of elderly for the first half of the 21st century. According to projections, the elderly in the age group 60 and above is expected to increase from 71 million in 2001 to 179 million in 2031, and further to 301 million in 2051; in the case of those 70 years and older, they are projected to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
60
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 6 publications
1
60
0
Order By: Relevance
“…3 In India, the population Z60 years is expected to increase by 2.5-fold in 30 years (projected from 71 million in 2001 to 177.5 million in 2031). 4 INDEYE study have reported the prevalence of wet AMD in India to be 1.2%. 1 This prevalence is low as compared with the western populations.…”
Section: Introductionmentioning
confidence: 99%
“…3 In India, the population Z60 years is expected to increase by 2.5-fold in 30 years (projected from 71 million in 2001 to 177.5 million in 2031). 4 INDEYE study have reported the prevalence of wet AMD in India to be 1.2%. 1 This prevalence is low as compared with the western populations.…”
Section: Introductionmentioning
confidence: 99%
“…In India, 8% of total population are above 60 years in 2010 and is likely to rise to 21% by 2050. 3 Further, OA has been associated with heavy physical occupational activity, a required livelyhood for many people living in rural communities in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…The geriatric population is composed of persons over 65 years of age and very few studies are available on the dermatologic diseases in this group [1]. In India, there were 72 million elderly persons above 60 years of age as of 2001 and this number is likely to increase to 179 million in 2031 and hence dermatologic care in geriatric population needs emphasis [2]. The dermatology practice of the future will see an increase in the number of geriatric patients [3] and geriatric health care has become a major international issue [4].…”
Section: Introductionmentioning
confidence: 99%